Case-Based Learning dalam Pembelajaran Akuntansi Sektor Publik - Komang Adi Kurniawan Saputra; Ni Made Intan Priliandani; Putu Dian Pradnyanitasari; Gde Deny Larasdiputra (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2019)
This study aims to examine the effect of the application of case-based learning methods and motivation on the understanding of public sector accounting with emotional intelligence as a moderator. The population of this study is undergraduate accounting department students who have taken public sector accounting courses at Warmadewa University. The sampling technique in this study was purposive sampling with certain criteria such as students who have taken public sector accounting courses. Research design is survey research design by distributing questionnaires to respondents. Data analysis uses moderated regression analysis (MRA). The results of this study indicate that the application of case-based and motivational learning methods significant positive effect on the understanding of public sector accounting, and proved that emotional intelligence is able to moderate the effect of the application of case-based learning methods and motivation towards understanding public sector accounting.